INDUSTRI KREATIF PAPAN SURFING BERBAHAN BAKU KAYU - Nawawi, Imam; Solichin, Solichin; Muksar, Makbul; Sumanto, Sumanto; Kusmayanto, Djoko Dwi (ABDIMAS PEDAGOGI, 2017)
Abstract: The science and technology program for export products (IbPE) is focused on two industrial activities, namely: (1) production activity in UKM Bomantara Art (UKM 1); and (2) UKM Sade Universal Art (UKM 2) located in Pacitan City East Java. Problems experienced by both UKM are: (1) regarding the need for supporting machines to make products more ergonomic, precision and symmetry; (2) on the improvement of Security, Health and Safety (K3); and (3) improvement of management pattern of product marketing management, human resource management and financial management and management which need to be improved by its standard and quality. The objective of this collaborative science and technology program is to scale up production through engineering, manufacturing, and improve the quality of UKM production and improve the pattern of marketing management, human resources and financial management. The results of IbPE program in the third year is the procurement of supporting machines for UKM Partners namely: (1) waste production elimination machine / device; (2) internet facility and catalog; and (3) procurement of product websites.Keywords: creative industry, surf board, woodAbstrak: Program iptek bagi Produk Ekspor (IbPE) ini difokuskan pada dua tempat kegiatan industri, yaitu: (1) kegiatan produksi di UKM Bomantara Art (UKM 1); dan (2) UKM Sade Universal Art (UKM 2) yang terletak di Kota Pacitan Jawa Timur. Permasalahan yang dialami kedua UKM tersebut adalah: (1) mengenai kebutuhan akan mesin pendukung agar produk lebih ergonomis, presisi dan simetri; (2) mengenai peningkatan Keamanan, Kesehatan, dan Keselamatan Kerja (K3); dan (3) peningkatan pola manajemen baik manajemen pemasaran produk, manajemen sumber daya manusia serta manajemen dan pengelolaan keuangan yang perlu ditingkatkan standar dan kualitasnya. Tujuan dari program iptek kerjasama ini adalah untuk meningkatkan skala produksi melalui rekayasa, manufaktur, dan meningkatan kualitas produksi UKM tersebut serta memperbaiki pola manajemen pemasaran, sumberdaya manusia serta pengelolaan keuangan. Hasil program IbPE di tahun ketiga ialah pengadaan mesin-mesin penunjang untuk UKM Mitra yakni: (1) mesin/perangkat eliminasi limbah produksi; (2) fasilitas internet dan katalog; dan (3) pengadaan website produk.Kata kunci: industri kreatif, papan surfing, kayu